Wages and Employment: The Role of Occupational Skills - Esther Mirjam Girsberger; Miriam Rinawi; Matthias Krapf (Institute of Labor Economics (IZA), 2018)
How skills acquired in vocational education and training (VET) affect wages and employment is not clear. We develop and estimate a search and matching model for workers with a VET degree. Workers differ in interpersonal, cognitive and manual skills, while firms require and value different combinations of these skills. Assuming that match productivity exhibits worker-job complementarity, we estimate how interpersonal, cognitive and manual skills map into job offers, unemployment and wages. We find that firms value cognitive skills on average almost twice as much as interpersonal and manual skills, and they prize complementarity in cognitive and interpersonal skills. The average return to VET skills in hourly wages is 9%, similar to the returns to schooling. Furthermore, VET appears to improve labour market opportunities through higher job arrival rate and lower job destruction. Workers thus have large benefits from acquiring a VET degree.
Keywords: E24; J23; J24; J64; 330; occupational training; vocational education; labor market search; sorting; multidimensional skills